Revisiting social responsibility as a characteristic feature of social interactions in various fields - В. Yu. Ashinov; А. R. Kumpilova (Вестник Майкопского государственного технологического университета, 2024)
The relevance of the research topic is determined by the fact that social responsibility seems to be an important condition for the stability of social order and development. During the periods of crisis, the problem of leveling social responsibility among individuals and communities arises. The purpose of the research is to identify the most significant areas of social life of a modern man in the 21st century, where social responsibility is considered as a significant category that requires particularly close scientific analysis. When working with empirical material, methods applied in Sociology of culture and Sociology of management have been used - axiological, typological, structural-functional ones. Based on the results of the research, it has been revealed that research into the implementation of social responsibility in the sphere of economic relations - business and corporate interactions - is most in demand. Scientists are also interested in the need to demonstrate social responsibility in the field of Biotechnology and activities of engineers, who should focus not only on the scientific and technical, but also on the humanitarian component of production. In the current information society, the social responsibility of the media is of particular importance. The key conclusions include theses that social responsibility as a way of positively responding to the requests of those in need (individuals, groups, society) is being formed very slowly due to various historical, socio-economic, general cultural and psychological reasons; social responsibility is difficult to manage, it cannot be formed under compulsion; it is necessary to find a balance of economic benefits and ethical altruistic values that are embedded in the religious and traditional systems of ethnic cultures.